SnO2Gold Nanoparticle@Polyhedral Oligomeric Silsesquioxane Hybrid Scaffolds in Microfluidic Format – Highly Efficient and Green Catalytic Platforms (Eur. J. Inorg. Chem. 7/2016). Issue 7 (March 2016) - Scholder, Pascal; Hafner, Martina; Hassel, Achim W.; Nischang, Ivo
Abstract : The cover picture shows the conceptual approach to miniaturized flow chemistry enabled by highly porous hybrid materials created in situ from polyhedral oligomeric silsesquioxanes (POSS). The materials contain gold nanoparticles that are strongly held within their porous structure by thiol–gold interactions. The tubular reactors are operated with an aqueous liquid phase at room temperature. The size of the gold nanoparticles and the pore size of the scaffolds themselves can be tailored to create highly efficient platforms for small‐scale chemical processes using the "green" solvent water. Details are discussed in the Communication by I. Nischang et al. onp. 951 ff . For more on the story behind the cover research, see theCover Profile .